Beyond Charge Balance: Counter‐Cations in Polyoxometalate Chemistry - Misra, Archismita; Kozma, Karoly; Streb, Carsten; Nyman, May (Angewandte Chemie (International ed.), 2020)
Polyoxometalates (POMs) are molecular metal‐oxide anions applied in energy conversion and storage, manipulation of biomolecules, catalysis, as well as materials design and assembly. Although often overlooked, the interplay of intrinsically anionic POMs with organic and inorganic cations is crucial to control POM self‐assembly, stabilization, solubility, and function. Beyond simple alkali metals and ammonium, chemically diverse cations including dendrimers, polyvalent metals, metal complexes, amphiphiles, and alkaloids allow tailoring properties for known applications, and those yet to be discovered. This review provides an overview of fundamental POM–cation interactions in solution, the resulting solid‐state compounds, and behavior and properties that emerge from these POM–cation interactions. We will explore how application‐inspired research has exploited cation‐controlled design to discover new POM materials, which in turn has led to the quest for fundamental understanding of POM–cation interactions. Supporting and lead roles: Beyond the classic roles of counter‐cations for polyoxometalates (POMs), there is emerging and compounding evidence that they drive reactivity; template cluster growth and supramolecular assembly; and endow POMs and POM materials with function. This Review covers both the classic and emerging roles of counter‐cations in fundamental and applied POM science.